Nucelar deterrence : the wohlstetter-blackett debate revisited - Rajesh, Basrur (2014)
The Cold War debate between Albert Wohlstetter and Patrick Blackett over the requirements of effective deterrence is of profound relevance half a century later. The two thinkers offered systematic arguments for their maximalist (Wohlstetter) and minimalist (blackett) positions. How we conceive of these requirements shapes the kinds of nuclear weapons doctrines, forces and postures we adopt. Whereas the Wohlstetter-Blackett debate was based largely on deductive logic, the opposing arguments can today be assessed on the basis of evidence drawing from nearly seven decades of strategic behaviour between nuclear rivals. An analysis of major confrontations in five nuclear dyads – United States-soviet union, United States-China, Soviet union-China, India-Pakistan, and United States-North korea – clearly offers much stronger support for Blackett’s minimalist case than for Wohlsetter’s maximalist one. Effective deterrence does not require second-strike capability as define by wohlstetter and the nuclear balance has no effect on a state’s capacity to deter. Consequently, the central tenets of orthodox nuclear deterrence theory and doctrine are shown to be without foundation. For policymakers, the optimal forces and postures required for effective deterrence are therefore less demanding and the hurdles in the path of arms control and at least partial disarmament less difficult to cross.